2014
DOI: 10.1097/mao.0000000000000495
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Ear Canal Cholesteatoma in Congenital Aural Atresia/Stenosis

Abstract: Approximately 1 in 5 patients with congenital aural stenosis were found to have ear canal cholesteatoma. Female sex is a risk factor; basic audiometric parameters provide no diagnostic utility in distinguishing ears with cholesteatoma from those without cholesteatoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 9 publications
1
18
0
3
Order By: Relevance
“…Previous studies analysing the clinical features of CAS involved small sample sizes, and no studies focused on the stability of the hearing outcomes567. This study uses the largest sample of CAS, providing guidance in consultation and emphasizing important aspects for long-term follow-up.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies analysing the clinical features of CAS involved small sample sizes, and no studies focused on the stability of the hearing outcomes567. This study uses the largest sample of CAS, providing guidance in consultation and emphasizing important aspects for long-term follow-up.…”
mentioning
confidence: 99%
“…Patients with stenosis sizes of 2 mm or less are at high risk for developing cholesteatoma and should undergo surgery; however, the data in the present study challenged this viewpoint. To date, there are no large sample studies focusing on the clinical features and long-term outcomes of CAS, and no studies have described the important parameter of measuring the diameter of EAC 5 6 7 8 9 10 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Cole and Jahrsdoerfer 17 reported external auditory canal cholesteatoma in 48 per cent of ears with congenital aural stenosis. A study by Casale et al 18 reported that 19 per cent of ears with congenital aural stenosis had acquired ear canal cholesteatoma. We found a significant association between external auditory canal cholesteatoma formation and Schuknecht type A (stenotic type) external auditory canals ( p = 0.03).…”
mentioning
confidence: 99%
“…Patients with stenosis sizes of 2 mm or less are at high risk for developing cholesteatoma and should undergo surgery; however, the data in the present study challenged this viewpoint. To date, there are no large sample studies focusing on the clinical features and long-term outcomes of CAS, and no studies have described the important parameter of measuring the diameter of EAC [5][6][7][8][9][10][11] . The aim of the present study was to comprehensively evaluate the clinical features and long-term outcomes of CAS, and challenge the previous viewpoint.…”
mentioning
confidence: 99%